Pharmacological Screening of Viola odorata L. for Memory-Enhancing Effect via Modulation of Oxidative Stress and Inflammatory Biomarkers - Saleem, Uzma; Hira, Sundas; Anwar, Fareeha; Shah, Muhammad Ajmal; Bashir, Samia; Baty, Roua S.; Badr, Reem H.; Blundell, Renald; Batiha, Gaber El-Saber; Ahmad, Bashir (Frontiers in Pharmacology, 2021)
Purpose: Alzheimer disease (AD) is a progressive neurodegenerative disorder that is caused by neuroinflammation and oxidative stress. The present study aimed to characterize and then investigate the memory-enhancing potential of Viola odorata methanolic extract in lipopolysaccharide (LPS) treated mice. Methods: Viola odorata characterization was done by using the GC-MS technique. Neuroinflammation was induced by the intracerebroventricular administration of LPS at a dose level of 12µg. Animals were divided randomly into six groups (n=10). Group I was normal control, given vehicle. Group II was disease control, received LPS (12 µg) via intracerebroventricular route. Group III was standard, administered donepezil (3µg) orally for 21 days. Group IV-VI were treatment groups, administered extract at 100, 200 and 400 mg/kg dose levels orally respectively for 21 days. Group III-VI received LPS (12µg) on the first day along with their treatments. During the treatment, the animals were assessed for memory retention by employing different behavioral paradigms namely, elevated plus maze, passive avoidance, foot shock and open field. Various mediators (endogenous antioxidants, neurotransmitters and acetylcholinesterase (AChE), involved in the pathogenesis of AD were quantified through UV spectrophotometric method. Results: Extract treated groups showed a remarkable improvement in cognitive impairment in all behavioral paradigms. Oxidative stress biomarkers i.e. superoxide dismutase, catalase, glutathione and acetylcholine esterase were raised dose-dependently in the treatment groups with a dose-dependent decrease in the malonaldehyde and AChE levels in the brains of treated animals. Treatment groups showed a decrease in the levels of inflammatory biomarkers i.e. Tumor necrosis factor-alpha, nuclear factor kappa-light-chain-enhancer of activated B cells and cyclooxygenase which supports the therapeutic effectiveness of the treatment. Conclusion: Based on behavioral, oxidative stress biomarkers and neuro-inflammatory data, it is concluded that Viola odorata possessed memory-enhancing activity and may prove a beneficial role in the management of AD.